(untitled) (Journal of Applied Oral Science, 2023)
The cases of ear malformations, conductive, mixed, and single-sided deafness hearing loss are candidates for surgery and use of Bone-Anchored Hearing Aids (BAHA). Commonly, the literature highlights two procedures to assess the benefits and characteristics of amplification in users: functional gain (FG) and effective gain (EG). Objective: Estimate and compare the EG and the FG to evaluate the benefits obtained by users of BAHA and, later, to compare tests of speech perception in silence and in noise. Methodology: The sample (n=79) was divided into four groups, implanted from February 2014 to February 2021. The following tests were analyzed: pure-tone audiometry by air and bone; research of audiometric thresholds in free field; speech perception tests in silence and in noise. Results: EG presented lower values than FG in all frequencies. The positive results of the speech perception tests were correlated with worse FG values. EG is the best method for evaluation, as it allows a proper comparison between devices, as well as a comparison with the prescription of validated rules. Conclusions: A better evaluation of results was observed on the EG values, indicating that it is a relevant method to assess auditory performance. In addition, the FG results were incompatible with the benefits obtained in the speech perception tests, showing that it is not a reliable tool for monitoring the results with the use of BAHA.